Beyond Retributive: Exploring the Participatory Paradigm in the Ferdi Sambo Trial - Fitryantica, Agnes; Mutalib, Abdul; Azimattara, Muchammad Daing; Sutrisno, Andri; Satriadi (Jurnal Cakrawala Hukum, 2024)
The participatory paradigm offers a different perspective on crime and justice. Instead of focusing solely on punishment, this paradigm emphasizes restoration, dialogue, and reconciliation. Applying the participatory paradigm could be a breakthrough in the context of high-profile criminal cases such as Ferdy Sambo, providing a more comprehensive and sustainable solution. The research problem in this study is that applying the participatory paradigm in the legal process of high-profile criminal cases like the Ferdi Sambo trial can shift the retributive approach within Indonesia’s criminal justice system. It also explores the advantages and disadvantages of implementing the participatory paradigm in high-profile criminal cases like the Ferdi Sambo trial in Indonesia. The case of Ferdi Sambo, a police general in Indonesia involved in a murder scandal, sparked extensive debate and analysis regarding the participatory paradigm in the context of law enforcement and justice. In this context, the participatory paradigm involves various parties in decision-making and law enforcement processes. Implementing the participatory paradigm in science and legal philosophy has several advantages, such as enhancing inclusivity, transparency, and legitimacy by involving multiple stakeholders in knowledge production and legal processes. However, this approach also has drawbacks, including challenges in balancing public participation with the objectivity of the judicial process, potential conflicts of interest, and maintaining the integrity of the legal system.